The NU-HOME RCT Home Food Environment, Family Meal Frequency, Meal Quality and Children’s Dietary Intake and Physical Activity Outcomes - Jayne A. Fulkerson; Melissa Horning; Sarah Friend; Eydie Kramer-Kostecka; Daheia J. Barr-Anderson; Rebecca Lindberg; Rebecca L. Freese; Colleen Flattum; Christie Martin (Appetite, 2026)

Stomatal Decoupling From Photosynthesis Under High Temperatures Is Consistent With Stomatal Optimisation - Simon R. G. Jones; Georg Wohlfahrt; Andrew D. Friend; Peter J. Franks; Alexander W. Cheesman; Lucas A. Cernusak; Haoyu Diao; Xiaolong Feng; Josef Urban; Tyeen Taylor; Martijn Slot; Lina M. Mercado; et al. (Global Change Biology, 2026)
Stomatal pores on plant leaves regulate the gain of carbon through photosynthesis and the loss of water through transpiration. Through their responses to environmental conditions, stomata can constrain plant productivity and transpiration fluxes, exerting a strong control on climate feedbacks over land. Although mechanistic modelling of stomata remains a challenge, semi‐empirical and optimisation models have been successfully applied to improve the simulation of land‐atmosphere fluxes of water and carbon. Optimisation approaches assume that some aspect of plant function, such as photosynthesis or growth rate, is optimised with respect to an environmental constraint, such as available soil water. Both optimisation models and semi‐empirical models predict that stomatal conductance will increase in concert with rising photosynthetic rates as temperatures approach a thermal optimum, beyond which declines in both photosynthesis and stomatal conductance are expected. However, a growing number of experiments have found that while photosynthesis declines beyond its thermal optimum, stomatal conductance often continues to increase at high temperatures. Early modelling work suggests that this phenomenon can be captured and explained by an optimal thermoregulation strategy via increased evaporative cooling at the leaf surface. However, many stomatal conductance models that are embedded within climate and Earth System Models do not correctly account for this feedback and so cannot capture observed decoupling. Here, we demonstrate that if leaf temperature is calculated iteratively outside the optimisation scheme, as is commonly done in Earth System Models, stomatal decoupling will not be captured. However, by calculating leaf temperature in parallel with optimal stomatal conductance, we find that we are able to capture observed decoupling and improve predicted leaf temperature and gas exchange. Correctly implementing the leaf energy balance equation within stomatal optimisation models will be essential for capturing high temperature responses of forests across the globe.

Gilbert’s Potoroo and the fun-guys: Co-existing mycophagous mammals as indicators of potentially available fungal food resources - Rebecca J. Quah; James Anthony Friend; Aaron J. Brace; Saul J. Cowen; Robert A. Davis; Harriet R. Mills; Anna J. M. Hopkins (Biodiversity and Conservation, 2025)

Forecasting the performance of alternative sheep production systems grazing perennial pastures - Christine E. Storer; Sosheel S. Godfrey; Susan M. Robertson; Michael A. Friend; Karl Behrendt (Agricultural Systems, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Short-term equine interaction for reducing test anxiety and facilitating coping skill development in college students during examination periods: A preliminary study - K. Everett; M.M. Friend; E. Farnlacher; A. Hilliard; M.C. Nicodemus; C.A. Cavinder; K. Holtcamp; D. Jousan (Journal of Equine Veterinary Science, 2024)

Remnant kenngoor (Phascogale calura) retain genetic connectivity and genetic diversity in a highly fragmented landscape - Rhiannon S. J. de Visser; Michelle Hall; Kym Ottewell; Jennifer C. Pierson; Angela Sanders; J. Anthony Friend; Laurence Berry; Carolyn Hogg; Renee A. Catullo (Conservation Genetics, 2024)
Kenngoor ( Phascogale calura ) persist in < 1% of their original distribution, occupying highly fragmented remnant habitat in south-west Western Australia, with very little known of the genetic diversity of the remaining wild populations. Recently, the species has been translocated to managed reserves to improve its conservation. Understanding genetic structure and patterns of genetic diversity is crucial to inform conservation translocations for species recovery. This study aims to (1) assess genetic structure and genetic diversity across remaining wild locations, (2) assess long-term genetic outcomes of a mixed-source wild-to-wild translocation, and (3) estimate global effective population size. We genotyped 209 samples from 13 locations of fragmented remnant habitat using reduced representation sequencing. An isolation by distance model best explained genetic structure across the survey areas, with evidence of fine scale divergence of two northern locations. Allelic richness and autosomal heterozygosity measures indicated that diversity is spread uniformly across locations, and no locations showed signs of inbreeding or strong genetic drift. The mixed-source translocation has retained the diversity of the wider species ten years post-translocation. Overall, our results suggest that connectivity between survey areas has largely been maintained and that no location has substantially lower genetic diversity, despite the highly fragmented nature of remnant kenngoor habitat. Future translocations should aim to represent a mixture of genetically divergent locations to maintain the diversity present at the species level. Ongoing conservation management will be required to ensure the long-term viability of the species in this fragmented landscape.

Parent Weight, Diet, Active Living, and Food-Related Outcomes of the Family-Focused:NU-HOME Randomized Controlled Trial - Melissa L. Horning; Sarah Friend; Rebecca L. Freese; Daheia J. Barr-Anderson; Jennifer A. Linde; Abbey Sidebottom; Samantha A. Sommerness; Jayne A. Fulkerson (Journal of the Academy of Nutrition and Dietetics, 2023)

175 Does short-term equine interaction within a collegiate environment provide students with perceived coping skills for test anxiety during examination periods? - A. Hilliard; M. Friend; C. Cavinder; M. Nicodemus; K. Holtcamp; D. Jousan (Journal of Equine Veterinary Science, 2023)

Food Insecurity and Parent Feeding Practices in Urban and Rural Children Aged 7–12 Years - Kristin M. Elgersma; Christie L. Martin; Sarah Friend; Jiwoo Lee; Melissa L. Horning; Jayne A. Fulkerson (Journal of Nutrition Education and Behavior, 2023)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Consistent limitation of growth by high temperature and low precipitation from range core to southern edge of European beech indicates widespread vulnerability to changing climate - A. J. Hacket-Pain; L. Cavin; A. D. Friend; A. S. Jump (European Journal of Forest Research, 2016)

Lack of in vitro–in vivo correlation for a UC781-releasing vaginal ring in macaques - Christopher McConville; James M. Smith; Clare F. McCoy; Priya Srinivasan; James Mitchell; Angela Holder; Ron A. Otten; Salvatore Butera; Gustavo F. Doncel; David R. Friend; R. Karl Malcolm (Drug Delivery and Translational Research, 2015)

Effect of four different reflective barriers on black-globe temperatures in calf hutches - T. H. Friend; J. A. Haberman; W. R. Binion (International Journal of Biometeorology, 2014)

Usefulness of an aluminized polyester film for reducing heat in polyethylene calf hutches - W. R. Binion; T. H. Friend; G. A. Holub (International Journal of Biometeorology, 2014)

Cephalopod remains from stomachs of sperm whales ( Physeter macrocephalus ) that mass‐stranded along the Oregon coast - James T. Harvey; Theresa Friend; Elizabeth A. McHuron (Marine Mammal Science, 2014)
On 16 June 1979, a herd of 41 sperm whales stranded near the mouth of the Siuslaw River in Florence, Oregon. The stomach contents from 32 whales were collected, identified to the lowest taxonomic level possible, enumerated, and measured. A total of 20,247 cephalopod lower beaks that represented 24 species from 14 different families were recovered. The most numerous species were Histioteuthis hoylei (25.9%), Taonius borealis (12.9%), Galiteuthis phyllura (11.2%), Gonatopsis / Berryteuthis type (10.9%), and Moroteuthis robusta (10.7%). Reconstructed estimates of mass indicated that M. robusta contributed almost 50% of the total mass of cephalopods consumed, followed by H. hoylei (19.3%), and T. borealis (7.0%). The most important species in the diet of stranded whales were M. robusta , H. hoylei , T. borealis , G. phyllura , Octopoteuthis deletron , and Gonatopsis/Berryteuthis type. There were significant differences in the diet of males and females, but no differences between sperm whales of different age groups. Overall, sperm whales primarily consumed small cephalopods that were likely eaten south of 45ºN in or near the California Current System. This study provides new estimates of the food habits of sperm whales in the northeast Pacific from one of the largest strandings of this species.

Is There a Role for Nitric Oxide in Methamphetamine-Induced Dopamine Terminal Degeneration? - Danielle M. Friend; Ashley N. Fricks-Gleason; Kristen A. Keefe (Neurotoxicity Research, 2014)

Efficacy of reflective insulation in reducing heat stress on dairy calves housed in polyethylene calf hutches - B. H. Carter; T. H. Friend; S. M. Garey; J. A. Sawyer; M. B. Alexander; M. A. Tomazewski (International Journal of Biometeorology, 2014)

Cp G inclusion in feed reduces sea lice, L epeophtheirus salmonis , numbers following re‐infection - S L Purcell; S E Friend; J M Covello; A Donkin; D B Groman; J Poley; M D Fast (Journal of Fish Diseases, 2013)
Lepeophtheirus salmonis infections in Atlantic salmon, S almo salar , have been characterized by little to no hyperplastic response and a biphasic immune response that results in chronic inflammation with tissue repair as the infection progresses. We hypothesized that C p G administration with prior lice exposure would enhance epithelial inflammatory mechanisms and boost the A tlantic salmon immune response to L . salmonis , leading to greater protection against infection. We administered multiple exposures of L . salmonis to two groups of A tlantic salmon and compared responses against first‐time exposed A tlantic salmon. Following re‐exposure, C p G fed fish exhibited increased skin expression of interleukin ( IL )‐1β and IL ‐12 β compared to control previously exposed ( CPE ) and control first‐time exposed ( CFE ) animals, respectively. This inflammatory enhancement occurred with significantly lower expression of matrix metalloproteinase‐9 ( MMP 9), both systemically (spleen) and locally (skin). Reduced MMP 9 expression was a hallmark of the re‐infected fish (occurred in both tissues at both times). When significant differences were present in the skin or spleen, the two re‐exposed groups showed greater similarity than with the first exposure group. Lice numbers on C p G fed fish were significantly lower than CFE fish at 7 days post‐re‐infection (dpri), and although they were not significantly different at 17 dpri, the trend of lower lice levels remained. CpG fed fish also showed nearly twofold greater protection than CPE when compared to the CFE group (48.5% vs. 27.0% reductions at 7 dpri and 27.2% vs. 13.1% reductions at 17 dpri, respectively). The enhanced protection of C p G oligodeoxynucleotide administration to previous exposure was consistent across all body surfaces and suggests that C p G can not only enhance innate responses to L . salmonis in A tlantic salmon, but also further stimulate adaptive responses.

Simulating forest productivity along a neotropical elevational transect: temperature variation and carbon use efficiency - Toby R. Marthews; Yadvinder Malhi; Cécile A. J. Girardin; Javier E. Silva Espejo; Luiz E. O. C. Aragão; Daniel B. Metcalfe; Joshua M. Rapp; Lina M. Mercado; Rosie A. Fisher; David R. Galbraith; Joshua B. Fisher; Norma Salinas‐Revilla; et al. (Global Change Biology, 2012)
A better understanding of the mechanisms controlling the magnitude and sign of carbon components in tropical forest ecosystems is important for reliable estimation of this important regional component of the global carbon cycle. We used the JULES vegetation model to simulate all components of the carbon balance at six sites along an Andes‐Amazon transect across Peru and Brazil and compared the results to published field measurements. In the upper montane zone the model predicted a lack of forest vegetation, indicating a need for better parameterization of the responses of cloud forest vegetation within the model. In the lower montane and lowland zones simulated ecosystem productivity and respiration were predicted with reasonable accuracy, although not always within the error bounds of the observations. Model‐predicted carbon use efficiency in this transect surprisingly did not increase with elevation, but remained close to the ‘temperate’ value 0.5. Upper montane forests were predicted to allocate ~50% of carbon fixation to biomass maintenance and growth, despite available measurements showing that they only allocate ~33%. This may be explained by elevational changes in the balance between growth and maintenance respiration within the forest canopy, as controlled by both temperature‐ and pressure‐mediated processes, which is not yet well represented in current vegetation models.

Source apportionment of ultrafine and fine particle concentrations in Brisbane, Australia - Adrian J. Friend; Godwin A. Ayoko; E. Rohan Jayaratne; Milan Jamriska; Philip K. Hopke; Lidia Morawska (Environmental Science and Pollution Research, 2012)

Waves and weathering at 3.7 Ga: Geological evidence for an equitable terrestrial climate under the faint early Sun - A. P. Nutman; V. C. Bennett; C. R. L. Friend (Australian Journal of Earth Sciences, 2012)

Species, genomes, and section relationships in the genus Arachis (Fabaceae): a molecular phylogeny - S. A. Friend; D. Quandt; S. P. Tallury; H. T. Stalker; K. W. Hilu (Plant Systematics and Evolution, 2010)

Seawater-like trace element signatures (REE + Y) of Eoarchaean chemical sedimentary rocks from southern West Greenland, and their corruption during high-grade metamorphism - C. R. L. Friend; A. P. Nutman; V. C. Bennett; M. D. Norman (Contributions to Mineralogy and Petrology, 2008)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

13C labeling of plant assimilates using a simple canopy-scale open air system - Alan F. Talhelm; Samir A. Qadir; Matthew D. Powers; Kate L. Bradley; Alexander L. Friend; Kurt S. Pregitzer (Plant and Soil, 2007)

Making water flow: a comparison of the hydrodynamic characteristics of 12 different benthic biological flumes - Per R. Jonsson; Luca A. van Duren; Muriel Amielh; Ragnhild Asmus; Rebecca J. Aspden; Darius Daunys; Michael Friedrichs; Patrick L. Friend; Frédéric Olivier; Nick Pope; Elimar Precht; Pierre-Guy Sauriau; et al. (Aquatic Ecology, 2006)

Surface macrofabric of boulder dominated desert mountain slopes, California, USA - Donald A. Friend (Journal of Mountain Science, 2005)

Soil carbon dioxide partial pressure and dissolved inorganic carbonate chemistry under elevated carbon dioxide and ozone - N. J. Karberg; K. S. Pregitzer; J. S. King; A. L. Friend; J. R. Wood (Oecologia, 2005)

?The Influence of Land Use Change On Global-Scale Fluxes of Carbon from Terrestrial Ecosystems? - P. E. Levy; A. D. Friend; A. White; M. G. R. Cannell (Climatic Change, 2004)

Abyssal peridotites >3,800 Ma from southern West Greenland: field relationships, petrography, geochronology, whole-rock and mineral chemistry of dunite and harzburgite inclusions in the Itsaq Gneiss Complex - C. Friend; V. Bennett; A. Nutman (Contributions to Mineralogy and Petrology, 2002)

Modelling canopy CO 2 fluxes: are ‘big‐leaf’ simplifications justified? - A. D. Friend (Global Ecology and Biogeography, 2001)
The ‘big‐leaf’ approach to calculating the carbon balance of plant canopies is evaluated for inclusion in the ETEMA model framework. This approach assumes that canopy carbon fluxes have the same relative responses to the environment as any single leaf, and that the scaling from leaf to canopy is therefore linear. A series of model simulations was performed with two models of leaf photosynthesis, three distributions of canopy nitrogen, and two levels of canopy radiation detail. Leaf‐ and canopy‐level responses to light and nitrogen, both as instantaneous rates and daily integrals, are presented. Observed leaf nitrogen contents of unshaded leaves are over 40% lower than the big‐leaf approach requires. Scaling from these leaves to the canopy using the big‐leaf approach may underestimate canopy photosynthesis by ~20%. A leaf photosynthesis model that treats within‐leaf light extinction displays characteristics that contradict the big‐leaf theory. Observed distributions of canopy nitrogen are closer to those required to optimize this model than the homogeneous model used in the big‐leaf approach. It is theoretically consistent to use the big‐leaf approach with the homogeneous photosynthesis model to estimate canopy carbon fluxes if canopy nitrogen and leaf area are known and if the distribution of nitrogen is assumed optimal. However, real nitrogen profiles are not optimal for this photosynthesis model, and caution is necessary in using the big‐leaf approach to scale satellite estimates of leaf physiology to canopies. Accurate prediction of canopy carbon fluxes requires canopy nitrogen, leaf area, declining nitrogen with canopy depth, the heterogeneous model of leaf photosynthesis and the separation of sunlit and shaded leaves. The exact nitrogen profile is not critical, but realistic distributions can be predicted using a simple model of canopy nitrogen allocation.

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

The high‐latitude terrestrial carbon sink: a model analysis - A. White; M. G. R. Cannell; A. D. Friend (Global Change Biology, 2000)
Summary A dynamic, global vegetation model, hybrid v4.1 ( Friend et al . 1997 ), was driven by transient climate output from the UK Hadley Centre GCM (HadCM2) with the IS92a scenario of increasing atmospheric CO 2 equivalent, sulphate aerosols and predicted patterns of atmospheric N deposition. Changes in areas of vegetation types and carbon storage in biomass and soils were predicted for areas north of 50°N from 1860 to 2100. Hybrid is a combined biogeochemical, biophysical and biogeographical model of natural, potential ecosystems. The effect of periodic boreal forest fires was assessed by adding a simple stochastic fire model. Hybrid represents plant physiological and soil processes regulating the carbon, water and N cycles and competition between individuals of parameterized generalized plant types. The latter were combined to represent tundra, temperate grassland, temperate/mixed forest and coniferous forest. The model simulated the current areas and estimated carbon stocks in the four vegetation types. It was predicted that land areas above 50°N (about 23% of the vegetated global land area) are currently accumulating about 0.4 PgC y −1 (about 30% of the estimated global terrestrial sink) and that this sink could grow to 0.8–1.0 PgC y −1 by the second half of the next century and persist undiminished until 2100. This sink was due mainly to an increase in forest productivity and biomass in response to increasing atmospheric CO 2 , temperature and N deposition, and includes an estimate of the effect of boreal forest fire, which was estimated to diminish the sink approximately by the amount of carbon emitted to the atmosphere during fires. Averaged over the region, N deposition contributed about 18% to the sink by the 2080 s. As expected, climate change (temperature, precipitation, solar radiation and saturation pressure deficit) and N deposition without increasing atmospheric CO 2 produced a carbon source. Forest areas expanded both south and north, halving the current tundra area by 2100. This expansion contributed about 30% to the sink by the 2090 s. Tundra areas which were not invaded by forest fluctuated from sink to source. It was concluded that a high latitude carbon sink exists at present and, even assuming little effect of N deposition, no forest expansion and continued boreal forest fires, the sink is likely to persist at its current level for a century.

Detection of a novel missense mutation and second recurrent mutation in the CACNA1A gene in individuals with EA-2 and FHM - K.L. Friend; D. Crimmins; T.G. Phan; C.M. Sue; A. Colley; V.S.C. Fung; J.G.L. Morris; G.R. Sutherland; R.I. Richards (Human Genetics, 1999)

Detection of a novel missense mutation and second recurrent mutation in the CACNA1A gene in individuals with EA-2 and FHM - K.L. Friend; D. Crimmins; T.G. Phan; C.M. Sue; A. Colley; V.S.C. Fung; J.G.L. Morris; G.R. Sutherland; R.I. Richards (Human Genetics, 1999)

Mitochondrial DNA sequence variation within the remnant populations of the endangered numbat (Marsupialia: Myrmecobiidae: Myrmecobius fasciatus ) - L. Fumagalli; C. Moritz; P. Taberlet; J. A. Friend (Molecular Ecology, 1999)
The numbat has been reduced to two populations in Western Australia. To better understand the effects of range reduction on gene flow and genetic variation, and to address questions crucial for the species’ management, we analysed mitochondrial DNA (mtDNA) sequences of free‐ranging individuals and museum specimens. The results suggest recent connectivity between the remnant populations, although one of those may have lost significant amounts of genetic diversity during the recent population size reduction. We propose that for management purposes the remnant populations should be treated as a single historical lineage and that, subject to certain caveats, consideration should be given to population augmentation by translocation.

Guar Gum-Based Sustained Release Diltiazem - Syed A. Altaf; Karen Yu; Jagdish Parasrampuria; David R. Friend (Pharmaceutical Research, 1998)

U-Pb zircon geochronological evidence for Neoproterozoic events in the Glenfinnan Group (Moine Supergroup): the formation of the Ardgour granite gneiss, north-west Scotland - C. R. L. Friend; P. D. Kinny; G. Rogers; R. A. Strachan; B. A. Paterson (Contributions to Mineralogy and Petrology, 1997)

Sectional notes - L. M. Ware; Frank Garrett; John L. Toevs; W. B. Ward; Verne C. Beverly; J. C. Campbell; C. A. Henderson; W. C. Barnes; John Noonan; W. H. Friend (American Journal of Potato Research, 1946)

Sectional notes - Ernest Marx; A. H. Eddins; Eugene W. Whiteman; W. B. Ward; P. T. Ecton; Marx Koehnke; J. C. Campbell; K. W. Lauer; W. H. Friend (American Journal of Potato Research, 1944)

Sectional notes - E. Marx; A. H. Eddins; G. D. Ruehle; H. L. Cochran; A. C. Moreau; J. V. Pace; Marx Koehnke; J. C. Campbell; M. E. Gardner; E. R. Jackman; C. A. Henderson; K. W. Lauer; et al. (American Journal of Potato Research, 1943)

Sectional notes - L. M. Ware; E. Marx; M. A. Lindsay; C. H. Metzger; H. L. Cochran; E. R. Bennett; A. C. Moreau; Frank W. Hussey; H. A. Reiley; Marx Koehnke; J. C. Campbell; M. E. Gardner; et al. (American Journal of Potato Research, 1943)

Sectional notes - E. Marx; C. H. Metzger; A. H. Eddins; W. B. Ward; John S. Gardner; A. C. Moreau; Frank W. Hussey; H. A. Riley; A. G. Tolaas; J. V. Pace; Marx Koehnke; E. V. Hardenburg; et al. (American Journal of Potato Research, 1943)

Sectional notes - Carl H. Metzger; W. B. Ward; H. L. Cochran; J. B. R. Dickey; A. B. Strand; W. H. Friend; H. H. Zimmerley; G. S. Ralston (American Journal of Potato Research, 1939)